Unique dancing call book. - Link, Charles (Rochester, N.Y., C. Link, 1893)
This unique document contains the prompter's calls for twenty-eight dances. The calls themselves are printed in large type, making them easier to read. No dance instructions are provided.
Cover title.
Printed parallel with back.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance -- Handbooks, manuals, etc; Dance Instruction and Technical Manuals; Prompting Quadrilles